FACTORS IN DEVELOPING CRITICAL THINKING SKILLS IN PRIMARY SCHOOL STUDENTS WITHIN THE EDUCATIONAL PROCESS (International Conference on Education, Psychology and Humanities, 2026)
The development of critical thinking skills in primary school students has become one of the most important objectives of modern education. In an era characterized by rapid technological advancement, information overload, and global interconnectedness, the ability to analyze, evaluate, and synthesize information is essential. This article explores the key factors influencing the formation of critical thinking skills among primary school learners within the educational process. It examines psychological, pedagogical, methodological, social, and technological dimensions that contribute to effective critical thinking development. Special attention is given to teacher competence, learning environment, curriculum design, instructional strategies, assessment approaches, and family involvement. The article also discusses the role of active learning methods such as problem-based learning, collaborative learning, questioning techniques, and reflective practices. Based on contemporary educational research and theoretical perspectives, this study highlights practical recommendations for fostering critical thinking in early education settings. The findings suggest that a systematic, learner-centered, and supportive educational environment significantly enhances the development of critical thinking skills in young learners.
Keywords: critical thinking, primary education, learner-centered approach, problem-based learning, formative assessment, pedagogical strategies, cognitive development, classroom environment.